The Effect of Acupressure on Pain and Anxiety Caused by Venipuncture. Issue 6 (November 2015) - Hosseinabadi, Reza; Biranvand, Shoorangiz; Pournia, Yadollah; Anbari, Khatereh
Abstract : The aim of this study was to determine the effect of massage of acupoints on pain and anxiety caused by venipuncture. In this double-blind clinical trial, 187 patients who were admitted to a hospital in Khorramabad, Iran, were selected and randomly divided into 3 groups: acupressure, placebo, and control. Blood samples were obtained twice from each patient in the 3 groups: once by the routine method from the left arm and once by performing interventions from the right arm. Results showed significant differences in pain scores ( P = .004) between the 3 groups after the intervention only. No significant differences between the 3 groups were found after the intervention with regard to pulse rate, systolic blood pressure, or diastolic blood pressure ( P > .05). The application of acupressure at the right acupoints may relieve pain caused by venipuncture. Although further studies are needed to confirm the findings of this study, it is recommended that nurses use this safe method to increase quality of nursing care and patient satisfaction.